2011
DOI: 10.1111/j.1469-8137.2011.03677.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding of lichenized fungi demonstrates high identification success in a floristic context

Abstract: Summary• Efforts are currently underway to establish a standard DNA barcode region for fungi; we tested the utility of the internal transcribed spacer (ITS) of nuclear ribosomal DNA for DNA barcoding in lichen-forming fungi by sampling diverse species across eight orders.• Amplification of the ITS region (ITS1-5.8S-ITS2) was conducted for 351 samples, encompassing 107, 55 and 28 species, genera and families, respectively, of lichenized fungi. We assessed the ability of the entire ITS vs the ITS2 alone to discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(133 citation statements)
references
References 78 publications
1
114
0
Order By: Relevance
“…In Aspergillus, ITS sequences are identical in several complexes of critical mycotoxigenic, industrial, and medically important species, and additional markers are necessary (52). Although the ITS region is a potentially effective DNA barcode in several lichenized lineages (53), genetic drift may prevent lineage sorting of ancestral polymorphisms in some slowly evolving groups.…”
Section: Discussionmentioning
confidence: 99%
“…In Aspergillus, ITS sequences are identical in several complexes of critical mycotoxigenic, industrial, and medically important species, and additional markers are necessary (52). Although the ITS region is a potentially effective DNA barcode in several lichenized lineages (53), genetic drift may prevent lineage sorting of ancestral polymorphisms in some slowly evolving groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although in some cases the ITS region has been shown to be effective for molecular identification using DNA barcoding (Kelly et al 2011;Schoch et al 2012), including species within the Rhizoplaca melanophthalma species-complex, the reliance on a single locus for inferring relationships and circumscribing species is problematic because the history of a single gene might not be representative of the organismal history. Within the R. melanophthalma species-complex relationships among species-level lineages are largely unsupported in the ITS topology ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…the sample coverage of the group (Roe et al 2010;Kelly et al 2011;Kiss 2012;Orock et al 2012;Schoch et al 2012).…”
mentioning
confidence: 99%
“…Schoch et al, (2012) found the ITS region to be among the markers with highest probability of correct identifications for a very broad group of sampled fungi. Additional fungal studies have provided support for the ITS region as a suitable fungal barcode (Seena et al, 2010;Dentinger et al, 2011;Kelly et al, 2011). Moreover, most environmental surveys (metagenomic studies) of fungi are using the ITS region in their studies (e.g.…”
Section: Colonization Rates and Spore Populationmentioning
confidence: 99%